Elephants on Acid: The Most Outrageous Experiments from the History of Science - Boese, Alex (London Pan Books, 2009)
Have you ever wondered if a severed head retains consciousness long enough to see what happened to it? Or whether your dog would run to fetch help, if you fell down a disused mineshaft? And what would happen if you were to give an elephant the largest ever single dose of LSD? The chances are that someone, somewhere has conducted a scientific experiment to find out...'Excellent accounts of some of the most important and interesting experiments in biology and psychology' Simon SinghIf left to their own devices, would babies instinctively choose a well-balanced diet?Discover the secret of how to sleep on planesWhich really tastes better in a blind tasting - Coke or Pepsi?
Keywords: Science; History